Export entry and network interactions evidence from the Belgian production network - Emmanuel Dhyne; Philipp Ludwig; Hylke Vandenbussche (National Bank of Belgium, 2023)
Low export participation of firms across countries is typically related to high entry costs allowing only the most productive firms to serve foreign markets. In this paper, we move beyond individual firm characteristics to explain export participation and investigate whether firms' domestic network linkages can facilitate export entry. Firms receive information from business interactions with experienced exporters which lowers sunk entry costs and allows them to enter the foreign market. Using rich data of buyer-seller linkages in the Belgian production network, we find that network heterogeneity is a key determinant of the extensive margin of trade. Each additional export signal received via network linkages increases the entry probability by 0.4 - 1.6 percentage points, giving firms with suitable networks a key advantage in accessing foreign markets. The marginal impact of network effects decreases in network size which we attribute to negative assortative matching in the underlying network formation process.
Keywords: F14; 330; export; learning about demand; networks